An Analysis of Students’ Mathematical Curiosity in Online Learning Viewed from Academic Level and Gender - Zetriuslita, Zetriuslita; Saleh, Sitti Fithriani; Baharullah, Baharullah; Laelasari, Laelasari (Research in Social Sciences and Technology- OpenED Network, 2024)
Online learning affects students' curiosity, so it is important to develop students' curiosity during the pandemic. The purpose of this study is to describe and analyze students' curiosity about online learning. This study was conducted in the Department of Mathematics Education during the odd semester 2021/2022 with 106 students in three different courses. The research instrument was a mathematical curiosity questionnaire administered to students using the Google Documents application. The data analysis technique used was descriptive analysis. The results showed that the general curiosity of the students is classified as